Prioritization of petroleum supply chains’ disruption management strategies using combined framework of BSC approach, fuzzy AHP and fuzzy Choquet integral operator - Ghasemzadeh, Fatemeh; Pishdar, Mahsa; Antuchevičienė, Jurgita (Journal of Business Economics and Management, 2017)
Industries in every sector have observed tangible losses from a broad range of disruptions during recent years. Factors such as globalization and outsourcing have made supply chains more sophisticated and this makes disruption management more necessary. Any disruption in each part of supply chain makes the whole supply chain face derangement and at last, ultimate customers realize the shaped disadvantages. Since avoidance of disruption occurrence is not always possible, application of different strategies with the aid of minimization of negative effects seems necessary. That is why in this paper, different strategies for disruption management in petroleum products supply chain and suitable criteria for prioritizing them are recognized via Balanced Score Card approach measures. After that, by application of fuzzy Analytical Hierarchy Process and intuitionistic fuzzy Choquet integral operator, their priorities are specified in order to make a guideline for managers to set proper plans and manage such disruptions more accurately.